A proposed approach to streamline the imposition of interest in tax refund cases (2022)
When one owes money to another, it is usual to pay interest. But when the government owes money to a taxpayer for exacting a tax it has erroneously or illegally collected, interest is generally not imposed. Jurisprudence has provided two rules on this subject: (1) that the govemment is not obliged to pay interest because there is no statutory provision that directs it ("No Statutory Authority Test") to do so; and (2) interest may only be imposed in case there is arbitrariness ("Arbitrariness Test"). This Note discusses the concepts of tax refunds and interest, and the prevailing laws and jurisprudence on the matter. It also shows, upon examination of the text not just of the Tax Code but all other statutes and case law on the imposition of interest, that the No Statutory Authority Test is not a proper justification to preclude the imposition of interest in tax refund cases. The Arbitrariness Test continues to be the most appropriate standard used in determining whether it is appropriate in each case to impose interest. This Note proposes a more streamlined set of guidelines on the imposition of interest using the Arbitrariness Test, considering the cardinal principle of due process of law and comparative judicial review standards for arbitrary and
capncious acts.
Keywords: Tax refunds; Tax returns -- Lawsuits & claims